ANALISIS BIBLIOMETRIK INVESTASI ASING LANGSUNG TERKAIT PENELITIAN PARIWISATA BERBASIS DATABASE ILMIAH SCOPUS - Simatupang, Parhimpunan (FEB Universitas Sam Ratulangi Manado, 2024)
This paper aims to analyse scientific research trends on Foreign Direct Investment (FDI) through bibliometric studies. This paper extensively investigates all articles published through Scopus regarding FDI in the Tourism context. The author found 275 papers that met the function, subject, and requirements using the phrases Foreign Direct Investment (FDI) and Tourism. The author used Vos Viewer as an analysis tool and the Scopus website database was chosen as the research data source. Publications related to the FDI concept found in the 2013-2023 period based on the Scopus index database showed a significant increase in 2019. As economic globalization continues to develop, interest in foreign direct investment (FDI) has also increased. The highest number of publications in the last ten years occurred in 2023. Judging from the country of origin of the publications, China is the leading country in terms of the number of authors, universities, number of documents, citations and research collaborations related to FDI. Current research trends are summarized into four cluster maps that can illustrate future research directions: Economic Analysis, air transportation, environmental policy, and economic growth. The approach taken by Zupic & Čater conceptually influences the framework for building dimensions and indicators used to measure FDI. The author only focuses on collecting publication data from the Scopus database, so research with other data sources may produce different research patterns to this FDI bibliometric research. This research presents a concise overview of bibliometric studies on FDI and provides recommendations for future research directions in mapping theme and subtheme clusters. Currently, research examining FDI in the context of tourism is still very limited, specially complete insights regarding the literature review of FDI in the export context. Key Words : Analisis Bibliometrik, Foreign Direct Investment, Tourism, Scopus, Vos viewer.